High-risk melanoma with nodal involvement in a young woman. - Khan, O; Middleton, M (2006)
BACKGROUND: An 18-year-old female presented to her General Practitioner with a bleeding mole on her back. The mole had been present since childhood but had started to bleed in the past month. She was otherwise asymptomatic with no relevant previous medical history. Physical examination revealed a 1.5 cm 1.7 cm pigmented lesion on the left aspect of the patient's upper back. There was no palpable lymphadenopathy. INVESTIGATIONS: Physical examination, excision biopsy, sentinel lymph node biopsy, CT scan of chest, abdomen and pelvis. DIAGNOSIS: Stage IIIB (T3bN2aM0) focally ulcerated, nodular malignant melanoma (Breslow depth 2.5 mm, Clark's level IV). MANAGEMENT: Wide re-excision, completion dissection of the left axillary lymph node, adjuvant high-dose interferon with maintenance interferon.